2020
DOI: 10.1186/s13148-020-00935-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic approach in obesity: DNA methylation in a prepubertal population which underwent a lifestyle modification

Abstract: Background Metabolically healthy obesity (MHO) is a considerably controversial concept as it is considered a transitory condition towards the development of different pathologies (type 2 diabetes, insulin resistance, or cardiovascular disease). MHO is closely related to lifestyle and environmental factors. Epigenetics has become an essential biological tool to analyze the link between obesity and metabolic status. The aim of this study was to determine whether MHO status is conditioned by the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…Activated macrophages polarize towards various functional phenotypes [ 67 ]. Future targeting of specific epigenetic pathways in cardiovascular disease may, thus, offer exciting novel approaches for the treatment of disease [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated macrophages polarize towards various functional phenotypes [ 67 ]. Future targeting of specific epigenetic pathways in cardiovascular disease may, thus, offer exciting novel approaches for the treatment of disease [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases contribute from a multifactorial and complex interplay of genetic, environmental, and lifestyle factors [ 53 ]. Epigenetic changes can modify gene transcription by altering the accessibility of gene transcription machinery, and these changes are predisposed by factors of nutrition, inflammation, sex, age, and lifestyle changes [ 54 ]. Chronic exposure to novel lifestyle factors coinciding with disease mechanisms involving chronic low-grade systemic inflammation affects vascular health [ 2 ].…”
Section: Epigenetics and Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…The lnc-MEG3 provoked apoptosis of trophoblast cells via NF-κB and Bax/Bcl2 signaling pathways [9]; also, Yu et al declared that the lnc-MEG3 downregulation is involved in PE through suppression of migration, invasion, and EMT of placental trophoblast cells by TGF-β pathway inhibitors [5]. Epigenetic changes such as DNA methylation are in uenced by environmental factors including life style [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently suggested that the main factor contributing to varying degrees of obesity susceptibility may be epigenetics and gene expression [ 130 , 131 , 132 ]. First studies concerning the role of DNA methylation in obesity were conducted in 2013 by Xu et al, in which the authors identified several CpG sites and DNA methylation variances associated with obesity in young African Americans [ 133 ].…”
Section: Genetic Determinants Of Obesity In the Context Of The Endmentioning
confidence: 99%